Serum and adrena corticosteroids level and hematologic changes in anemic rats fed on iron deficient diet - Payawan, Adelina A.
The glucocorticoid activity in anemic, iron-deficient male rats of the Sprague-Dawley strain was studied by measuring changes in corticosterone levels in serum and the adrenals and by examining known peripheral effects of the corticosteroids. The lymphocyte count decreased significantly in the iron-deficient group while the polymorphonuclear leukocytes remained unchanged. The latter decreased significantly in the control groups. This resulted in a significantly lower lymphocyte: polymorphonuclear leukocyte ratio in the iron-deficient group as the anemia progressed. The total white blood cell count remained unchanged. The serum concentration of cholesterol and ascorbic acid significantly increased but that of corticosterone was reduced. At sacrifice, the adrenals were bigger relative to body weight and had higher concentrations of corticosterone, ascorbic acid and cholesterol compared to those of the iron-supplemented controls. In the iron-deficient group, the serum transcortin level was similar to those of the controls. These findings were interpreted as indicative of increased corticosterone synthesis in the adrenals, increased rate of corticosterone release from transcortin because of increased peripheral utilization of the steroid in the iron-deficient animals. There was no significant difference in the total serum protein and protein fractions separated electrophoretically between the different experimental groups. In the iron-deficient rats, no significant histopathologic changes could be discerned in the cells of the adrenals. In the spleen, more hemosiderin was observed in those of the irn-supplemented controls while more neutrophils were seen in those of the iron-deficient group